Prognostic role of epidermal growth factor receptors' expression in patients with i-ii stage of non-small cell lung cancer - A.P. Kolesnik; A.I. Shevchenko; V.A. Tumansky; A.V. Evseev; M.A. Shishkin (Zaporozhye State Medical University, 2013)
Introduction: According to the National Cancer Registry data, referring to the revised data in Ukraine, 17422 new cases of lung cancer and 13498 deaths from this malignant tumor were registered in Ukraine within 2010 [1]. Therefore, high level of incidence and low effectiveness of treatment require improvement of current diagnostic and treatment methods of lung cancer. Surgery is the main treatment method of lung cancer, which gives a chance to recover. However, even after surgical treatment disease progression develops in some patients, that denotes the biological diversity of patients with early stages of NSCLC. Molecular markers' use for prognostic groups' selection is one of the ways to solve the problem of individualized treatment. The most significant among great number of prognostic markers is the group of growth factor receptors [11]. In studied literature we found conflicting data on the prognostic role of epidermal growth factor receptors in patients with early-stage lung cancer. Objective: The aim of our work was to determine the connection of clinical and morphological patients' characteristics with the expression of epidermal growth factor receptors of 1 and 2 types (EGFR, HER-2-neu) and also to analyze the influence of these factors on patients survival with early stages (I-II) of non-small cell lung cancer (NSCLC). Materials and methods: 100 patients with early stages of NSCLC, who received treatment in Zaporozhye regional clinical oncological dispensary from June 2008 till June 2011, were recruited in this study. Among them there were 84 men (84%) and 16 women (16%). Mean age was 60,5 years (95% CI, 58,9-62,1). All patients received surgical treatment with subsequent microscopic examination of tumor tissue. Immunohistochemistry of the removed tumor was performed in all the patients to determine the expression of HER-2-neu, EGFR. Results: Lack of expression of HER-2-neu was observed in 114 patients (64,4%). Expression (+) was detected in 30 patients, (+ +) and (+ + +) in 18 and 8 patients, respectively. HER2/Neu expression wasn't detected in 7 patients. The absence of EGFR expression was observed in 13 patients. EGFR expression in 6-10% of cells (+) was observed in 15 patients, 10-50% (+ +) - in 31 patient, more than 50% (+ + +) - in 85 patients. In 33 patients the definition of EGFR expression was not carried out. There was no correlation between age, sex, tumor localization, histological type, tumor differentiation, pT and pN criteria with the level of HER-2-neu expression. Also, there was no correlation between age, sex, tumor localization, histological type, tumor differentiation, pT and pN criteria with the level of EGFR expression. One of the main criteria for prognostic value of the marker is its connection with survival. There was shown no difference between patients with lack or presence of HER-2-neu expression during connection analysis of cell staining intensity and survival in patients with І-ІІ stages of NSCLC and EGFR expression (log-rank = 0,18). However, there is a tendency toward an improvement in patients' survival with a lack of Her-2-neu expression. Multivariate regression analysis was performed to evaluate prognostic value of different clinical and morphological criteria. Independent prognostic factors are histological tumor type (HR=-2,44, p=0,01) and the size of primary tumor (HR=2,97, p=0,003). Prognostic value of other factors, including the expression of growth factors receptors, is not clinically significant, although the borderline predictive value of EGFR expression is noted. Conclusions: Therefore, considering the results of studies carried out in our clinic and the literature data, insufficient knowledge of epidermal growth factor receptors expression in patients with lung cancer is obvious. We have found no connection between clinical and morphological factors and overexpression of EGFR and HER-2-neu in patients with I-II stage of NSCLC.